Subvesical duct and hepaticocholecystic duct in one patient - Moon Soo Choi; Heenkenda Kotakadeniya (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Subvesical bile ducts (formerly known as "Ducts of Luschka") are a rare entity associated with bile leaks due to their proximity to the gallbladder bed. Failure to recognise their presence could lead to life-threatening complications to the patient in the form of an abdominal collection, biliary peritonitis and sepsis. We describe a patient with two abnormal ducts found in the gallbladder fossa which were managed surgically.